EU posted work and transnational action in the German meat industry. (May 2015) - Wagner, Ines
This article traces the course of a transnational action in the German meat industry involving an alliance of transnational posted workers, a local civil society organization and the trade union NGG (Gewerkschaft Nahrung-Genuss-Gaststätten). As labour's channels of influence have broken down and posting of low-wage workers has intensified, trade unionists have responded by building coalitions with societal actors. The case illustrates a complementary approach to studying how resistance unfolds in transnational workplaces under conditions in which traditional avenues for protest are blocked or marginalized.